Compensatory Hippocampal Neurogenesis in the Absence of Cognitive Impairment Following Experimental Hippocampectomy in Adult Rats - Cardoso, Giuliana T. M.; Gomes-Leal, Walace; Franco, Edna C. S.; Pereira, Antonio; Gomes, Francinaldo L.; Brino, Ana Leda F.; Lima, Silene M. A. (Frontiers in Cellular Neuroscience, 2021)
Temporal lobe epilepsy (TLE) is the commonest type of focal epilepsy in adult humans and hippocampal sclerosis (HE) is the main pathological finding in this type of epilepsy. In refractory TLE, patients are indicated for unilateral resection of the affected hippocampus by a surgical procedure called hippocampectomy which generally does not cause any cognitive impairment. Once adult hippocampus is a region of endogenous neurogenesis, even in elderly people, we have hypothesized that a compensatory increase in hippocampal neurogenesis might occur in the remaining hippocampus after unilateral hippocampectomy. To test this hypothesis, we realized hippocampectomy surgery in adult Wistar rats to investigate possible compensatory neurogenic events as well investigate if procedure cause some kind of cognitive impairment. Eighteen Wistar rats were allocated to the following experimental groups: control (no surgery), G15 and G30 (n=6 per group). The surgical procedure was performed and adjacent cortex and hippocampus of the left hemisphere were completely removed, behavioral procedures were performed to address possible cognitive impairments. After 15 (G15) and 30 (G30) days the animals brains were collected and fixed. The histopathology was performed using thionine staining and mature neurons and migratory neuroblasts were immunolabeled using anti-NeuN and anti-doublecourtine (DCX) antibodies. We didn’t find any cognitive impairment in the animals after hippocampal removal that suggest that unilateral hippocampectomy didn’t cause any cognitive impairment in experimental groups. The remaining hippocampus presented a higher number of DCX positive cells them compared to control (p<0,001) that suggest a compensatory increase in endogenous neurogenesis in the contralateral hippocampus at both G15 and G30. This study using animal model is relevant to global understanding of the neural basis of compensatory neurogenesis that could explain the reasons why postoperative patients do not present cognitive deficit related to memory consolidation.